Secreted frizzled-related protein 4: An angiogenesis inhibitor - Muley, A.; Majumder, S.; Kolluru, G.; Parkinson, S.; Viola, H.; Hool, L.; Arfuso, Frank; Ganss, R.; Dharmarajan, Arunasalam; Chatterjee, S. (Elsevier Inc., 2010)
Wnt signaling is involved in developmental processes, cell proliferation, and cell migration. Secreted frizzled-related protein 4 (sFRP4) has been demonstrated to be a Wnt antagonist; however, its effects on endothelial cell migration and angiogenesis have not yet been reported. Using various in vitro assays, we show that sFRP4 inhibits endothelial cell migration and the development of sprouts and pseudopodia as well as disrupts the stability of endothelial rings in addition to inhibiting proliferation. sFRP4 interfered with endothelial cell functions by antagonizing the canonical Wnt/ß-catenin signaling pathway and the Wnt/planar cell polarity pathway. Furthermore, sFRP4 blocked the effect of vascular endothelial growth factor on endothelial cells. sFRP4 also selectively induced apoptotic events in endothelial cells by increasing cellular levels of reactive oxygen species. In vivo assays demonstrated a reduction in vascularity after sFRP4 treatment. Most importantly, sFRP4 restricted tumor growth in mice by interfering with endothelial cell function. The data demonstrate sFRP4 to be a potent angiogenesis inhibitor that warrants further investigation as a therapeutic agent in the control of angiogenesis-associated pathology. Copyright © American Society for Investigative Pathology.